Manipulating hydrogenation pathways enables economically viable electrocatalytic aldehyde-to-alcohol valorization - Ze-Cheng Yao; Jing Chai; Tang Tang; Liang Ding; Zhe Jiang; Jiaju Fu; Xiaoxia Chang; Bingjun Xu; Liang Zhang; Jin-Song Hu; Li-Jun Wan (Proceedings of the National Academy of Sciences, 2025)
Electrocatalytic reduction (ECR) of furfural represents a sustainable route for biomass valorization. Unfortunately, traditional Cu-catalyzed ECR suffers from diversified product distribution and industrial-incompatible production rates, mainly caused by the intricate mechanism−performance relationship. Here, we manipulate hydrogenation pathways on Cu by introducing ceria as an auxiliary component, which enables the mechanism switching from proton-coupled electron transfer to electrochemical hydrogen-atom transfer (HAT) and thus high-speed furfural-to-furfuryl alcohol electroconversion. Theoretical and kinetic analyses show that oxygen-vacancy-rich ceria delivers an efficient formation−diffusion−hydrogenation chain of H* by diminishing H* adsorption. Spectroscopic characterizations indicate that Cu/ceria interfacial perimeter enriches the local furfural, synergistically lowering the barrier of the rate-determining HAT step across the perimeter. Our Cu/ceria catalyst realizes high-rate HAT-dominated ECR for electrosynthesis of single-product furfuryl alcohol, achieving a high production rate of 19.1 ± 0.4 mol h −1 m −2 and a Faradaic efficiency of 97 ± 1% at an economically viable partial current density of over 0.1 A cm −2 . Our results demonstrate a highly efficient route for biofeedstock valorization with enhanced techno-economic feasibility.